DNA nanostructures constructed with multi-stranded motifs. Issue 6 (22nd February 2017) - Yang, Donglei; Tan, Zhenyu; Mi, Yongli; Wei, Bryan
Abstract: Earlier studies in DNA self-assembly have foretold the feasibility of building addressable nanostructures with multi-stranded motifs, which is fully validated in this study. In realizing this feasibility in DNA nanotechnology, a diversified set of motifs of modified domain lengths is extended from a classic type. The length of sticky ends can be adjusted to form different dihedral angles between the matching motifs, which corresponds to different connecting patterns. Moreover, the length of rigidity core can also be tuned to result in different dihedral angles between the component helices of a certain motif therefore different numbers of component helices. The extended set of motifs is used for self-assembly of complex one dimensional, two dimensional and three dimensional structures.